1972
DOI: 10.1104/pp.49.3.293
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Wall-degrading Endopolygalacturonase Secreted by Colletotrichum lindemuthianum

Abstract: Cultures of Colletotrichum lindertmuthianum (Saccardo and Magnus) Scribner have been induced to secrete an endopolygalacturonase (polygalacturonide glyeanohydrolase EC3.2. 1.15). This enzyme has been brought to a high state of purity bv ion exchange, gel filtration, and agarose affinity chromatography. The enzyme has optimal activity at pH 5, has an apparent molecular weight as determined bv gel filtration of about 70,000, and prefers polygalacturonic acid to pectin as its substrate. The enzymne, while hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
1
1

Year Published

1973
1973
1999
1999

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 19 publications
3
46
1
1
Order By: Relevance
“…The fact that the PGA lyases eluted after the included volume of the agarose column indicated that these enzymes have an affinity for the agarose matrix. Similar observations were made during the purification of endopolygalacturonases secreted by Colletotrichum lindemuthianum (12) and Rhizopus stolonifer (19).…”
Section: Resultssupporting
confidence: 58%
“…The fact that the PGA lyases eluted after the included volume of the agarose column indicated that these enzymes have an affinity for the agarose matrix. Similar observations were made during the purification of endopolygalacturonases secreted by Colletotrichum lindemuthianum (12) and Rhizopus stolonifer (19).…”
Section: Resultssupporting
confidence: 58%
“…The solubilization of wall components resulting from the action of the endopolygalacturonase on isolated sycamore cell walls is complete in 1 hr when 20 units of endopolygalacturonase are used for each 5 mg of walls (32). If the walls are de-esterified by treatment with base before the endopolygalacturonase treatment, the extent of the reaction is the same as with untreated walls.…”
Section: The Portion Of Sycamore Cell Walls Solubilized By Endopolygamentioning
confidence: 83%
“…The only purified enzyme that we have examined which is capable of appreciable degradation of intact cell walls is the endopolygalacturonase isolated from Colletotrichum lindemuthianum culture medium (32). The reaction of endopolygalacturonase with cell walls and the fractionation and characterization of the portion of the wall solubilized by the action of this enzyme are described below.…”
Section: The Portion Of Sycamore Cell Walls Solubilized By Endopolygamentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated that the oligogalacturonides with the highest specific elicitor activity were closely related, but not identical, to those obtained by partial acid hydrolysis of soybean cell walls and citrus pectin (28) and by treatment of polygalacturonic acid with endopolygalacturon-ical Co. D-GalUA was from Aldrich Chemical Co. and D-glucose was from Fisher Scientific Co. a-1 ,4-Trigalactosyluronic acid was prepared as described (12). Galactaric acid and a-D-GalUA-( 1 -* 4)-a-D-GalUA41 --4)-a-galactaric acid were prepared from D-GalUA and a-1 ,4-trigalactosyluronic acid, respectively, by bromine oxidation as described (33).…”
mentioning
confidence: 99%